Optimization of sustainable biodiesel production from waste cooking oil using heterogeneous alkali catalyst - Andrifar, M.; Goembira, Fadjar; Ulfah, Maria; Putri, Rika; Yuliarningsih, Rati; Aziz, Rizki (Jurnal Rekayasa Proses, 2022)
The increasing world population, rapid industrialization, urbanization, and economic growth have led to a continuous increase in the consumption of fossil fuels to meet the ever-increasing demand for energy. Continuous emissions from burning fossil fuels will create a need to find appropriate and sustainable substitutes for fossil fuels. Biodiesel is the right alternative solution for diesel engines because it is renewable, non-toxic, and environmentally friendly. Waste cooking oil (WCO) from the food, non-food, restaurant, and household sectors is produced on a large scale in every country and can contribute to environmental pollution if proper disposal systems are not applied. Instead of throwing it landfills Environmental pollution can be minimized by recycling WCO. This study evaluates the potential of using WCO to produce biodiesel using zeolite synthesized from fly ash as a heterogeneous alkali catalyst through a transesterification reaction. The reactor in this study used a 1,000 ml three-necked boiling flask equipped with a condenser, cooling tank, and pump. Stirring and heating during the process of biodiesel production using a magnetic stirrer and a hot plate. The thermometer is used to measure the reaction temperature. Optimization of biodiesel production from zeolite catalyst synthesized from fly ash based on variations in the ratio of methanol: oil (8:1; 10:1; 12:1; and 14:1), catalyst weight (1, 2, 3, and 4% weight), and temperature (45 oC, 55 oC, and 65oC). Zeolite from fly ash produces biodiesel with a yield of 91.67% with optimum operating conditions reaction time of 60 minutes, methanol oil ratio of 8:1, operating temperature 55oC, and the amount of catalyst 1% by weight. This experiment confirms the possibility of utilizing fly ash waste for the application of catalysts in biodiesel production.